Ipod Product Life Cycle / Nur Fadiyah Rahmat ... [et al.] - Rahmat, Nur Fadiyah; Zulkifli, Raziat; Suhaili, Azreena Syuziana (2016)
The iPod is a line of portable media players and multi-purpose pocket computers designed and marketed by Apple Inc. the first version was released on October 2001, about 8 months after iTunes (Macintosh version) was released. The most recent iPod redesigns were announced on July 15, 2015. There are three current versions of the iPod: the ultra-compact iPod Shuffle, the compact iPod Nano and the touchscreen iPod Touch. Like other digital music players, iPod can serve as external data storage devices. Storage capacity varies by model, ranging from 2 GB for the iPod Shuffle to 128 GB for the iPod Touch (previously 160 GB for the iPod Classic, which is now discontinued.) Apple's iTunes software (and other alternative software) can be used to transfer music, photo, videos, games, contact information, e-mail setting, Web bookmarks, and calendars to devices supporting these features from computers using certain versions of Apple Macintosh and Microsoft Windows operating systems. Before the release of iOS 5, the iPod branding was used for the media player included with the iPhone and iPad, a combination of the Music and Videos apps on the iPod Touch. As of iOS 5, separate apps named "Music" and "Videos" are standardized across all iOS-powered products. While the iPhone and iPad have essentially the same media player capabilities as the iPod line, they are generally treated as separate products. During the middle of 2010, iPhone sales overtook those of the iPod. In mid-2015, a new model of the iPod Touch was announced by Apple, and was officially released on the Apple store on July 15, 2015. The sixth generation iPod Touch includes a wide variety of spec improvements such as the upgraded A8 processor and higher-quality screen. The core is over 5 times faster than previous models and is built to be roughly on pair with the iPhone 5S. It is available in 5 different colors: Space grey, pink, gold, silver and red.